Improving Teachers' Access to Classroom Microcomputers. - Dean, Jay W. (Education Digest, 1982)
The article focuses on the issues related to the educational use of microcomputers in the U.S. As computers become better suited--both in design and in cost-to school purposes, the teacher's ability to use them effectively becomes more important. Hundreds of small software houses have sprung up in response to the need for good educational software. In some instances, their product is that of teachers who have the pedagogy and the subject matter in hand but lack the technical skills necessary to use the computer to the best advantage. One complication is that software developers often hesitate to send programs out for evaluation, because of the ease of illegal duplication. Evaluators should therefore be aware of how selected software relates to theories on learning, cognitive development, instructional psychology, and adaptive instruction. Evaluators must also know what computers are capable of providing. A second difficulty with educational use of computers is that no existing computer language is really suitable for teachers' use. While teachers have no need to become BASIC programmers, some proficiency in the language is necessary for those who want to cope with computers in the classroom. PILOT is a dialogues oriented computer language that deals nicely with words and text. Still missing is a language that is easy to learn and easy to use, one that resembles natural dialogue, allows for variations in style, and can be mastered in a few hours.